Phylogenetic analysis of congenital rubella virus from Indonesia: a case report - Elisabeth Siti Herini; Agung Triono; Kristy Iskandar; Albaaza Nuady; Lucia Hetty Pujiastuti; Marcellus; Andika Priamas Nugrahanto; Musthofa Kamal; Gunadi (BMC, 2022)
Abstract Background Rubella is a common inherited infection resulting in congenital cataracts and a significant cause of permanent vision loss in developing countries. In 2016, Indonesia had the highest number of congenital rubella syndrome (CRS) cases globally. Here, we report the first genotype of the rubella virus extracted from the eye lens from a child with congenital cataracts due to CRS. Case presentation A female neonate was delivered by an elective caesarean delivery with normal birth weight at term from a 24-year-old mother in the rural setting. The baby presented with bilateral congenital cataracts, small-moderate secundum atrial septal defect, severe supravalvular pulmonary stenosis, and profound bilateral hearing loss. She also had microcephaly and splenomegaly. The patient's serology showed persistent positive IgG for rubella virus at the age of four years and four months. Following extraction during cataract surgery, viral detection of the lenses identified the presence of rubella. Phylogenetic analysis confirmed that the virus was grouped into genotype 1E. Conclusions Our study reports the first phylogenetic analysis of the rubella virus extracted from the eye lens of a child with CRS in Indonesia. The detection of the rubella virus from eye lenses is remarkably promising. Our findings also emphasize the importance of molecular epidemiology in tracking the origin of rubella infection toward achieving virus eradication.